THE ROLE OF STATE IN THE CONSTRUCTION OF “OTHERNESS” IN MYANMAR: THE CASE OF ROHINGYA MUSLIMS - PANTEA, Ana (Studia Universitatis Babes-Bolyai Studia Europaea, 2019)
In the last four years, Myanmar has been the focal point of Southeast Asian politics. The democratization process started after the election of 2015, and the sanctions have been lifted in 2016, however, the Rohingya remained excluded legally, socially, economically and politically from the nation by discriminatory legislation (imposed since 1982). The present paper examines the evolution of perception toward this ethno-religious minority which takes the shape of organized pogroms in which the Rohingya are seen as enemies of the nation, as “the others”. The paper question as well the impact of the democratic process in providing human security for Myanmar’s ethno-religious minorities, without the active involvement of an inter-faith approach and civil initiatives.